Public order in times of crisis. A critical analysis of the use of the category of public order in the Spanish Constitutional Court response to the COVID-19 pandemic - García Ortiz, Adrián (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Despite its transcendence as an enabling clause for a state of emergency and, consequently, for the suspension of fundamental rights, the Spanish Constitutional Court, in its 148/2021 ruling, which declares the unconstitutionality of the state of alarm decreed for the management of the COVID-19 pandemic, resolves the meaning and scope of public order in a single paragraph and without support in its own jurisprudence. This paper tries to analyse the causes of legal technique that have led the Constitutional Court to conceive of public order in a broad sense and the risks that this entails, based on an analysis of the concept and characterisation of public order in general and, specifically, in Spanish law, in which two meanings of the term have coexisted: as a constitutional system of values and as democratic normality or absence of conflict.